2021
DOI: 10.3390/antiox10101523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypothermia and Allopurinol on Oxidative Status in a Rat Model of Hypoxic Ischemic Encephalopathy

Abstract: Hypoxic ischemic encephalopathy (HIE) is one of the main causes of morbidity and mortality during the neonatal period, despite treatment with hypothermia. There is evidence that oxidative damage plays an important role in the pathophysiology of hypoxic-ischemic (HI) brain injury. Our aim was to investigate whether postnatal allopurinol administration in combination with hypothermia would reduce oxidative stress (OS) biomarkers in an animal model of HIE. Postnatal 10-day rat pups underwent unilateral HI of mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Allopurinol, a xanthine oxidase inhibitor, is neuroprotective by reducing oxygen radical production and brain damage in experimental, animal and early human ischemia and reperfusion studies. An animal model study found [ 67 ] that protein oxidation and lipid peroxidation were significantly reduced when subcooling was combined with allopurinol treatment, thereby enhancing the neuroprotective effects of HIE. Similarly, a double-blind, placebo-controlled study (ALBINO, NCT03162653), [ 58 ] is currently investigating the neuroprotective effects of allopurinol in neonates with HIE.…”
Section: Medicationmentioning
confidence: 99%
“…Allopurinol, a xanthine oxidase inhibitor, is neuroprotective by reducing oxygen radical production and brain damage in experimental, animal and early human ischemia and reperfusion studies. An animal model study found [ 67 ] that protein oxidation and lipid peroxidation were significantly reduced when subcooling was combined with allopurinol treatment, thereby enhancing the neuroprotective effects of HIE. Similarly, a double-blind, placebo-controlled study (ALBINO, NCT03162653), [ 58 ] is currently investigating the neuroprotective effects of allopurinol in neonates with HIE.…”
Section: Medicationmentioning
confidence: 99%
“…In addition, its anti-oxidative potential has been shown in previous studies [ 11 ]. In this regard, Durán Fernández-Feijóo et al showed that allopurinol’s administration reduced oxidative stress and mitigated tissue injury in a rat model of hypoxic-ischemic encephalopathy [ 12 ]. Varrica et al loaded allopurinol into lipid nanoparticles and used them to treat skin wounds.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal encephalopathy is one of the main causes of morbidity and mortality in term infants, and there is evidence that oxidative damage plays an important role in the pathophysiology of hypoxic–ischemic brain injury. Recently, several studies have been conducted with the aim of providing adjacent neuroprotective and antioxidant therapeutic options complementary to hypothermia treatment, animal [ 7 , 8 , 9 ] and clinical [ 10 ] studies with different compounds. Kynurenic acid significantly reduced reactive oxygen species and antioxidant enzyme activity and enhanced GSH levels and hypoxic–ischemic conditions in a rat model [ 7 ].…”
mentioning
confidence: 99%
“…Only the highest concentration of kynurenic acid showed neuroprotection when applied 6 h after hypoxia–ischemia, and results indicated the induction of neuroprotection at the reactive oxygen species formation stage. In a different study, the capability of postnatal allopurinol administration in combination with hypothermia treatment to reduce oxidative stress biomarkers was assessed in a rat model of hypoxic–ischemic encephalopathy, showing that the administration of allopurinol, hypothermia, and the combination treatment protects the brain against oxidative damage [ 8 ]. Furthermore, in neonatal hypoxia ischemia complicated by perinatal infection, therapeutic hypothermia does not improve outcomes due to pre-existing oxidative stress and neuroinflammation, which shorten the therapeutic window.…”
mentioning
confidence: 99%